The Implementation of the Strict Liability Principle in Legal Liability of Artificial Intelligence in Indonesia's Healthcare Sector - Liana Salwa Irene; Christian Andersen (Eduvest - Journal of Universal Studies, 2025)
The rapid advancement of Artificial Intelligence (AI) has the potential to give rise to significant legal issues, particularly concerning AI legal liability. However, Indonesia has yet to enact specific regulations governing AI. This study aims to examine how legal liability is determined when AI is involved in legal disputes within the healthcare sector and to identify the application of the strict liability principle as a basis for legal liability for the impacts caused by AI in the healthcare field in Indonesia. This research employs a normative juridical method, utilizing statutory regulations as primary legal materials, and books, journals, research findings, as well as legal expert opinions as secondary legal materials. The findings indicate that AI is not yet specifically regulated in Indonesia; currently, legal liability can be pursued through Article 1367 of the Indonesian Civil Code. However, this provision does not fully guarantee the realization of legal justice in the context of AI-related liability. Therefore, it is imperative for Indonesia to promptly establish regulations concerning AI, and the adoption of the strict liability principle could be considered as one of the regulatory approaches.